RESPON PERTUMBUHAN DAN HASIL TANAMAN CABAI (Capsicum annum L.) TERHADAP PENGURANGAN DOSIS NPK 16:16:16 DENGAN PEMBERIAN PUPUK ORGANIK - Raisa Baharuddin (DINAMIKA PERTANIAN, 2016)
Low soil fertility in Riau impact on low production of chilli. The low production of chilli caused by improper application of fertilizer. The addition of organic matter has the potential to reduce the dose of inorganic fertilizers and improve soil fertility. This research aims to determine the response to growth and yield of chili on reduction of dose NPK 16:16:16 with organic fertilizer. This research was conducted from February to June 2016 at the Experimental Farm, Faculty of Agriculture, Islamic University of Riau. The research used a completely randomized design with 3 replications. Factors dose of NPK fertilizer consists of five levels i.e., without NPK, 100%, 75%, 50%, and 25% of the dose of NPK. Factors organic fertilizers consists of three levels i.e., chicken manure, liquid bioorganic, and chicken manure + liquid bioorganic. The results showed that chicken manure fertilizer or with the addition of liquid bioorganic fertilizer can reduce the NPK usage by up to 50% without affecting the growth and yield of chili. Reduction of dose NPK 16:16:16 up to 75% gave growth and yield not statistically different in the level of α 0:05 with 100% dose of NPK. Treatment of organic fertilizer (chicken manure or with liquid bioorganic fertilizer) significantly increased the growth and yield of chili on the level of α 0:05.